An evaluation of some assumptions underpinning the bidomain equations of electrophysiology - Whiteley, JP (Oxford University Press, 2019)
Tissue level cardiac electrophysiology is usually modelled by the bidomain equations, or the monodomain simplification of the bidomain equations. One assumption made when deriving the bidomain equations is that both the intracellular and extracellular space are in electrical equilibrium. This assumption neglects the disturbance of this equilibrium in thin regions close to the cell membrane known, as Debye layers. We first demonstrate that the governing equations at the cell, or microscale, level may be adapted to take account of these Debye layers with little additional complexity, provided the permittivity within the Debye layers satisfies certain conditions that are believed to be satisfied for biological cells. We then homogenise the microscale equations using a technique developed for an almost periodic microstructure. Cardiac tissue is usually modelled as sheets of cardiac fibres stacked on top of one another. A common assumption is that an orthogonal coordinate system can be defined at each point of cardiac tissue, where the first axis is in the fibre direction, the second axis is orthogonal to the first axis but lies in the sheet of cardiac fibres, and the third axis is orthogonal to the cardiac sheet. It is assumed further that both the intracellular and extracellular conductivity tensors are diagonal with respect to these axes, and that the diagonal entries of these tensors are constant across the whole tissue. Using the homogenisation technique we find that this assumption is usually valid for cardiac tissue, but highlight situations where the assumption may not be valid.